May Measurement Month 2018: an analysis of blood pressure screening results from Australia - Carnagarin, Revathy; Fonseca, Ricardo; Brockman, Derrin; Critchley, Sue; Tan, Isabella; Trengove, Naomi; Tan, Kearney; Lambert, Gavin W; Cowley, Diane; Burrell, Louise M; Poulter, Neil R; Beaney, Thomas; et al. (OXFORD UNIV PRESS, 2020)
May Measurement Month (MMM), originally initiated as a temporary solution to address the lack of blood pressure (BP) screening programs worldwide, emerged as an effective annual campaign to increase the awareness of hypertension. MMM18, a cross-sectional survey of volunteers aged ≥18 years was carried out during May 2018 predominantly in capital cities across Australia following the standard MMM protocol. Blood pressure screening along with additional information including anthropometric data and responses to questionnaires on demographic, lifestyle, and environmental factors were collected from 3 352 individuals across Australia. After multiple imputation, 1 026 (30.6%) adult Australians had hypertension. Of the 2 936 individuals not on antihypertensive treatment, 610 (20.8%) were hypertensive, and 237 (57.1%) of the 416 individuals receiving antihypertensive treatment had uncontrolled BP. In line with MMM17 results and other previous surveys, MMM18 revealed that close to one-third of the screened population (30.6%) had hypertension, 57.1% of individuals treated with BP-lowering medication remained uncontrolled indicating suboptimal management of the condition in the majority of patients. Most importantly, only 49.0% of those with hypertension were aware of their elevated BP, highlighting lack of awareness of elevated BP in nearly half of the affected population. Elevated BP was directly associated with alcohol consumption, overweight, and obesity. Our findings demonstrate the need for (i) continued efforts to increase BP awareness in the population, (ii) optimization of BP management strategies, and (iii) tackling some of the major contributors to BP elevation, including alcohol consumption and obesity.